Issues and dilemmas in career planning of medical students in Surat, India (Bangladesh Journal of Medical Science, 2013)
Background: In recent time issues of career choices in medical student has been gaining mounting attention. Aim: The current study was planned with an aim to understand issues and dilemmas in career planning of medical students in Surat city, India Methods: This is a cross-sectional study comprising of personal interviews using a self -designed structured questionnaire among 400 simple randomly selected medical students, interns and junior residents of Surat Municipal Institute of Medical Education and Research covering issues associated with their career concerns and future life. Data analysis was done with help of Epi Info 7. The study sample comprised of students 46.5%, intern doctors 36%, junior resident doctors 17.5%. Results:Females were more content with either a graduate or a post graduate degree, whereas males were more inclined towards pursuing super specialty degrees (P